Leadership and Organizational Commitment as Antecedents of Civil Servant Performance: A Mediating Analysis - Ratno Purnomo (Faculty of Economics and Business Universitas Jenderal Soedirman, 2021)
Empirical studies into leadership and organizational commitment have widely been conducted in private organizations, but a handful of the same research has been undertaken in non-profit organizations. The aim of this research was to examine the role of leadership and organizational commitment in predicting job performance in the context of government organization. The study used a sample of 197 persons, consisting of civil servants located in Central Java, Indonesia. The response rate was 78.8 percent. The independent variable comprises of leadership and organizational commitment, and job performance as dependent variables. Valid and reliable items were used for the variable measurement. Hierarchical regression analysis results showed three major findings for this research: first, transformational leadership directly and positively influences various dimensions of organizational commitment and job performance. In addition, transactional leadership produces a significant influence merely on normative commitment. Second, continuance commitment and normative commitment directly and positively influence job performance. Third, continuance and normative commitment have mediating effects in the relationship between leadership and job performance. Practical implications for local government and suggestions for future research are discussed at the end of the article